Estimating the impact of prenatal health care services on adverse pregnancy outcomes in Tanzania: a propensity score matching approach - Ntegwa, Magashi Joseph; Pelizzo, Riccardo (Frontiers in Global Women's Health, 2025)
IntroductionThe prevalence of adverse pregnancy outcomes remains one of the public issues that needs to be addressed in low- and middle-income countries (LMICs), including Tanzania. Despite evidence on the effectiveness of antenatal care (ANC) services in addressing adverse pregnancy outcomes, empirical studies are scarce. Therefore, this study aims to analyze the impact of ANC services on adverse pregnancy outcomes.MethodsThis is a retrospective study that uses secondary data from the Tanzania Demographic and Health Survey for 2022. The impact of ANC services on adverse pregnancy outcomes was estimated using Propensity Score Matching (PSM), and the robustness of results was checked using doubly robust estimatorsResultsAdequate ANC services utilization reduces adverse pregnancy outcomes in Tanzania. Specifically, adequate ANC services utilization reduces adverse pregnancy outcomes: 5.6%–8.2% (depending on the PSM approach used). Similarly, an adequate ANC package reduces adverse pregnancy outcomes: 6.3%–9.3% (depending on the PSM approach used).ConclusionsThe prevalence of adverse pregnancy outcomes needs to be addressed through adherence to ANC services utilization. Despite the utilization of ANC services being influenced by social, economic, and demographic factors, it is important to ensure essential packages of services are delivered to a pregnant woman for better pregnancy outcomes, as our results show that ANC visits alone have no significant impact.